A violência obstétrica sob o olhar de profissionais de saúde - Santos, Mayara Guimarães (2017)
Obstetric violence is a worldwide public health issue. It refers to all kind of violence originated during the assistance to pregnancy and puerperal cycle or abortion, perpetrated by health professionals in heath care institutions. The main objective of this research is to identify and to analyze the meanings of obstetric violence by physicians and obstetric nurses workers in public institutions for delivery care assistance. This is a qualitative approach of social and strategic research. The data were collected by semi-structured interviews with 13 professionals of two public institutions on delivery-care assistance in Goiânia, Goiás. The data from these interviews was analyzed by the Meaning Interpretation Method, which generated three theme categories. The first one, “Humanization of parturient assistance” the professionals reported the meaning and practices of the delivery care assistance humanization. In the second, “Living the obstetric violence”, are presented meanings of violence, its’ showings, being the care unworthy, body abuse, non-confidential care and discrimination the most expressive facts for these actions. The third category, “Knowledge about the pregnancy and puerperal cycle”, the interview participants reported a lack of knowledge of parturients about gestation, childbirth and puerperium, besides prenatal inefficiency to prepare pregnant women to childbirth. This research contributed for a better comprehension of meanings attributed to obstetric violence and provided subsidies for concrete actions related to this matter may be considered during public policy making, in order to face this phenomena and improve the quality of parturient assistance.